If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3u + -4 + 7 = 55 Reorder the terms: -4 + 7 + 3u = 55 Combine like terms: -4 + 7 = 3 3 + 3u = 55 Solving 3 + 3u = 55 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3u = 55 + -3 Combine like terms: 3 + -3 = 0 0 + 3u = 55 + -3 3u = 55 + -3 Combine like terms: 55 + -3 = 52 3u = 52 Divide each side by '3'. u = 17.33333333 Simplifying u = 17.33333333
| 0.6(5m+15)=-12 | | 7-3(5-3v)+9v=28 | | 2x-3+8=-27 | | 2x-3+8=27 | | -5y+x=-6 | | -2(n+3)=-12 | | 2y(4x+2y+3)= | | 32.45+1.468x=766.45 | | 2y-10=16 | | -5x+y=-6 | | 9+m*3=2 | | 169x^2-196x^2=0 | | 7x+12=10x+6 | | 4-(x+9)=-x-5 | | w-8+9=-29 | | (1+3b)=-20 | | w-8+9=29 | | X-109.3=184.9 | | 2x-14=x+9 | | 6(5z-8)-4=9+z | | -9+n*4=-7 | | 3x-6=-4 | | -8x=2x+20 | | 7(3x-10)=3(7x-5) | | 0.6x+22=28 | | 5.4X+.4=3.4 | | 7x+3-(2x-1)= | | 14y-8-10y=0 | | (Y-2)+y=18 | | .6k-.1k=.5k-1 | | x^5-3x^4+4x^3-8x^2+16=0 | | ln(6x-6)=13 |